(untitled) (REMUNOM, 2023)
Despite advances in public health regarding women’s health, breast cancer is still an incident neoplasm in the female population. Tocantins is the newest state in the federation and studies that show epidemiological particularities about women’s health are necessary. In this sense, the objective of this study was to highlight the profile of women affected by breast cancer between the years 2013 to 2021 using the DataSUS database as a reference. Our results showed that in the period studied, about 4% of the cases belonged to the north of the country, in which the most affected age group was between 35 and 69 years old, with the highest rate between 50 and 59 years old, presenting 4,101 cases (27.72% ) followed by 40 to 49 years and 60 to 69 years with 4,079 cases (25.57%) and 2,772 cases (18.73%), respectively. In addition, the state of Tocantins totaled 1,498 cases of breast cancer, in which the age group between 50 and 69 years was responsible for 687 cases (45.86%) and between 40 and 49 years culminated in 416 cases (27.77 %). Furthermore, 99,545 mammograms were performed in the state during the study period in order to obtain the diagnosis of breast cancer. In addition, a mortality rate of 7.5 deaths per 100,000 women between years. In conclusion, despite cervical cancer being described as the most frequent in the region, public policies are needed that incorporate measures to promote and prevent women’s health with regard to breast cancer screening in the state’s population. Key words: Breast cancer. Tocantins. Women’s health.